Implementasi Sistem Pendeteksi Tingkat Kematangan Buah Pepaya Menggunakan Metode RGB - Krista Bella Dwi Rahayu Nur Widyasari; Ulla Delfana Rosiani; Agung Nugroho Pramudhita (SMATIKA JURNAL : STIKI Informatika Jurnal, 2021)
To date, agriculture in Indonesia still uses a manual method to detect the ripeness of papaya fruits. Based on its characteristics, the source of the degree of fruit maturity is obtained from the raw, half ripe and ripe papaya fruit obtained from the farmer. Here after performing the implementation on the basis of the information obtained. To measure the logic for detecting the degree of fruit maturity, the RGB method here will be used. In accordance with what is needed, the results of the implementation itself should function well. Based on the calculation of the accuracy obtained on the system that was made it reached 50%.